Non-consistent changes and drivers of water-sediment fluxes in the yarlung tsangpo river basin of the Tibetan plateau - Dongmei Zhao; Donghong Xiong; Kunlong He; Baojun Zhang; Fan Zhang; Han Wu; Haiyan Fang; Wenduo Zhang; Changyan Zhou; Xiaodan Wang (International Soil and Water Conservation Research)
Variations in water-sediment fluxes and their driving mechanisms are critical to riverine ecosystems and management. Yet, current estimates of the response of water and sediment flux remain insufficiently quantified, limited by the scarcity of long-term hydrological records in the alpine regions. Here, we leverage decadal observations in the Yarlung Tsangpo River basin, to investigate the dynamic shifts in water-sediment fluxes from 1955 to 2020 and elucidate their linkage to a warming and wetting climate, snowmelt, and environmental greening (including natural- and human-induced greening) in the different spatial and temporal scale. Major drivers of shifts in water-sediment flux are identified by using wavelet coherence and variance partitioning of redundancy analysis. The results highlight that observational data from four gauging stations (i.e., Lhaze, Nugesha, Yangcun, and Nuxia) uncover a substantial decrease in Suspended Sediment Load (SSL) (Nuxia: 12.302 × 104 t/yr, P < 0.05) in the downstream with consistently increasing runoff and precipitation. Especially during the flood season (July to September), the dam/reservoir construction caused a median decrease in SSL. Dropping sediment offsets the slightly rising SSLs in the midstream and upstream (upper Yangcun: 14.8 × 104 t/yr, P > 0.05). Up to 80% of sediment was sourced from the middle stretch between Lhaze and Nugesha despite it supplied with lower regional runoff generation. Nevertheless, the downstream zone experienced the transition from a sediment source to a deposition area around 1998. We further found the negative and positive effects between water-sediment fluxes and revegetation, and demonstrated that employing NDVI to evaluate human-induced vegetation greening might overestimate the impact of ecological restoration programs on water-sediment fluxes. Attribution analysis indicates that precipitation was not the primary contributor to runoff and SSL changes in all stretches of the basin. In the upstream, temperature and associated snowmelt can be more important than precipitation. Compared to before 1998, precipitation is still the primary driver of change in downstream runoff change after 1998, whilst vegetation restoration, rather than precipitation, dominates the reduction in downstream SSL. These findings have far-reaching significance for watershed managers and decision-makers in terms of developing effective strategies for water resources and soil erosion control.